2023
DOI: 10.1017/s0261143023000041
|View full text |Cite
|
Sign up to set email alerts
|

Shaping rhythm: timing and sound in five groove-based genres

Abstract: Shaping events at the microlevel of rhythm is an important aspect of many groove-based musics. In the present study, we explore the interconnectedness of musical parameters such as timing, attack shape, timbre and relative intensity in creating groove through investigating musicians and producers’ discourse in five genres (jazz, samba, electronic dance music, hip-hop and traditional Scandinavian fiddle music). Through semi-structured interviews, we found both genre-specific accounts of how such musical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Groove is defined as the urge to move that is induced by specific rhythmic patterns or music (Madison, 2006;Senn et al, 2016). Similar terms for groove exist worldwide such as "nori" in Japanese (Kawase & Eguchi, 2010;Kawase, 2023), "balanço" in Brazilian (Danielsen et al, 2023), "lüpfig" in Swiss German (Senn et al, 2019), and numerous people share a common groove mechanism (reviewed in Etani et al, 2024). Several acoustic characteristics of music, such as syncopation (Witek et al, 2014;Witek et al, 2017), tempo (Etani et al, 2018), beat clarity (Madison et al, 2011), and bass component (Wesolowski & Hofmann, 2016), induce groove.…”
Section: Characteristics Of Groovementioning
confidence: 99%
“…Groove is defined as the urge to move that is induced by specific rhythmic patterns or music (Madison, 2006;Senn et al, 2016). Similar terms for groove exist worldwide such as "nori" in Japanese (Kawase & Eguchi, 2010;Kawase, 2023), "balanço" in Brazilian (Danielsen et al, 2023), "lüpfig" in Swiss German (Senn et al, 2019), and numerous people share a common groove mechanism (reviewed in Etani et al, 2024). Several acoustic characteristics of music, such as syncopation (Witek et al, 2014;Witek et al, 2017), tempo (Etani et al, 2018), beat clarity (Madison et al, 2011), and bass component (Wesolowski & Hofmann, 2016), induce groove.…”
Section: Characteristics Of Groovementioning
confidence: 99%
“…One emphasis has been to identify musical parameters that make PLUMM more likely. The investigation of rhythmic nuances or microtiming, a theory advocated for by the musical community and popular music studies (Berliner, 1994;Iyer, 2002;Danielsen, 2006;Danielsen et al, 2023;Bechtold et al, 2023), has yielded inconclusive evidence so far (Frühauf et al, 2013;Davies et al, 2013;Datseris et al, 2019;Câmara et al, 2020a;2020b). Rhythmic complexity, especially syncopation, is another well-researched musical parameter, and several studies showed that a medium degree of syncopation is associated with higher PLUMM (Witek et al, 2014;Sioros et al, 2014;Witek et al, 2017;Matthews et al, 2019;Stupacher et al, 2022;Spiech et al, 2022;Cameron et al, 2023;Zalta et al, 2024).…”
Section: On the Urge To Move To Musicmentioning
confidence: 99%
“…Yet, some polyphonic timbres are stronger associated with specific genres than others: distorted guitars, hissing cymbals, a high-pitched bass drum with a strong attack, and a screaming voice makes listeners think of heavy metal, rather than polka. In Danielsen et al (2023), music creators stress the importance of genre-typical timbre and how it shapes how our experiences feel. b) Acoustic level: timbre descriptors associated with perceptual timbre spaces In contrast to the semantic level, the acoustical side of timbre is objectively measurable.…”
Section: On Timbrementioning
confidence: 99%
See 2 more Smart Citations